2020
DOI: 10.1007/s11205-020-02562-x
|View full text |Cite
|
Sign up to set email alerts
|

Drying Climates and Gendered Suffering: Links Between Drought, Food Insecurity, and Women’s HIV in Less-Developed Countries

Abstract: HIV/AIDS represents the leading cause of death among women of reproductive age globally, and gender inequalities in the burden of HIV/AIDS are most pronounced in poorer countries. Drawing on ideas from feminist political ecology, we explore linkages between suffering from drought, food insecurity, and women's vulnerability to HIV. Using data from 91 less-developed countries, we construct a structural equation model to analyze the direct and indirect influence of these factors, alongside other socioeconomic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 34 publications
(80 reference statements)
3
36
0
1
Order By: Relevance
“…These findings also support that food security has a significant gender dimension, where women are both more at risk of severe hunger, and suffer more consequences due to limited coping strategies, which includes different forms of sexual activity in exchange for material support. 14 Finally, the inter-country heterogeneity of certain risk behaviors suggests that there might be multiple different pathways between food insecurity and HIV acquisition, and these are likely to be highly contextual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings also support that food security has a significant gender dimension, where women are both more at risk of severe hunger, and suffer more consequences due to limited coping strategies, which includes different forms of sexual activity in exchange for material support. 14 Finally, the inter-country heterogeneity of certain risk behaviors suggests that there might be multiple different pathways between food insecurity and HIV acquisition, and these are likely to be highly contextual.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The impact has been assumed to be gendered in that women are particularly vulnerable to income shocks and to disruption to access to health resources. 14 Food insecurity has also been associated with lower efficacy of antiretroviral treatment (ART) due to drug malabsorption or decreased adherence, with virologic failure. 15 As countries pursue the new UNAIDS 95-95-95 goals, weather extremes disrupting food production and supplies could jeopardize epidemic control, both in terms of increased risk behaviors, as well as disruption of treatment due to displacement or poverty, impacting access to testing and ART services.…”
Section: Introductionmentioning
confidence: 99%
“…Another pooled analysis of 19 population-based surveys in sub-Saharan Africa similarly showed that adolescent girls and unemployed women experienced higher rates of intimate partner sexual and physical violence in drought-affected communities [ 43 ]. A recent analysis of national vital statistics from 91 LMICs found that food insecurity mediated the association between drought and women’s HIV prevalence [ 44 ]. An advantage of the qualitative approach used in the current study is its capacity to situate intermediary variables, like early marriage or transactional sex, on the mechanistic pathway from food insecurity to sexual health outcomes in drought-affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change impacts broader environmental systems to increase strain on global food and water supplies. 2 13 14 Drought can increase food insecurity [15][16][17] and migration, [18][19][20] and disrupt both provision of-and access to-health services. 13 Food insecurity is associated with HIV acquisition risks through behavioural (eg, transactional sex) and mental health (eg, alcohol use, depression) pathways.…”
Section: Open Accessmentioning
confidence: 99%